Burden of uterine fibroids in Italy: epidemiology, treatment outcomes, and consumption of health care resources in more than 5,000 women [Corrigendum] - Chiumente M; De Rosa M; Messori A; Proli EM (Dove Medical Press, 2017)
Chiumente M, De Rosa M, Messori A, Proli EM, ClinicoEconomics and Outcomes Research. 2017;9:525–535On page 529, Ancillary study section, the 3rd sentence “Patients had a mean age of 45 years; Charlson index was about 1% and 10.9% after medical therapy underwent surgery” should have read “Patients had a mean age of 45 years and the Charlson index was about 1%; after medical therapy 148 patients (10.9%) underwent surgery”. Read the original article